Are molecular methods helpful for the diagnosis of Helicobacter pylori infection and for the prediction of its antimicrobial resistance? - Fernandez-Caso, Belen; Miqueleiz, Ana; Valdez, Verónica B.; Alarcón, Teresa (Frontiers in Microbiology, 2022)
Infections produced by Helicobacter pylori, a spiral Gram-negative bacterium, can cause chronic gastritis, peptic ulcer, and gastric cancer. Antibiotic therapy is the most effective treatment for H. pylori infection at present. However, owing to the increasing antibiotic resistance of H. pylori strains, it has become a serious threat to human health. Therefore, the accurate diagnosis of H. pylori infections and its antibiotic resistance markers is of great significance. Conventional microbiological diagnosis of H. pylori is based on culture, however successful isolation of H. pylori from gastric biopsy specimens is a challenging task affected by several factors and has limitations in terms of time of response. To improve conventional methods, some molecular techniques such as PCR have been recently used in both invasive and non-invasive H. pylori diagnosis, enabling simultaneous detection of H. pylori and point mutations responsible for frequent antibiotics resistance. The advantages and disadvantages of molecular methods, mainly PCR, versus conventional culture for the H. pylori identification and the detection of antibiotic resistance are discussed. As expected, the combination of both diagnostic methods will lead to the most efficient identification of the H. pylori strains and the resistance patterns.